The influence of Servive Quality and Corporate Image toward Customer Satisfaction at BPJS Ketenagakerjaan KCP Kendal - Dwi - Utami; Winarto - Winarto; Azizah - Azizah (Politeknik Negeri Semarang, 2020)
The aims of this research was to determine the influence of Service Quality and Corporate Image on Customers Satisfaction toward BPJS Ketenagakerjaan KCP Kendal. The methods of data collection are interview, questionnaires, and literature review. The questionnaires used is Differential Semantik with 5-point scale and the sample collection method is accidental sampling with 100 of customers at BPJS Ketenagakerjaan KCP Kendal. The analysis technique used in this research are validity test, reliability test, normality test, heteroskedastisity test, multicolinearity test, linearity test, multiple linear regression, t test, F test and coefficient of determination. Based on calculations using SPSS version 23, the result of this research showes that the regression equation was Y = 1,165 + 0,190 X1 + 0,453 X2. The result of this study explaines that the variable service quality and corporate image has positive and significant effect on customer satisfaction. The coefficient of determination in this research was 0,741, which means service quality and corporate image affect the variable of customer satisfaction by 74,1%, while the rest are influenced by other variables outside this regression model.